Understanding ion migration suppression in all-inorganic mixed halide perovskites via tin-lead alloying - Xinyu Li; Yanbo Shang; Xue Wang; Zhimin Fang; Tianao Hou; Dehan Li; Shuang Gao; Tao Chen; Xu Pan; Zhengguo Xiao; Shangfeng Yang (Nano Research Energy)
All-inorganic perovskites are advantageous in terms of improved thermal stability compared to organic-inorganic counterparts. However, the ion migration-induced hysteresis significantly undermines the long-term operational stability of all-inorganic perovskite solar cells (PSCs), particularly in mixed halide perovskites. Herein, we report that tin-lead (Sn-Pb) alloying for all-inorganic mixed halide perovskites can effectively inhibit the ion migration behavior, as comprehensively revealed by the time-of-flight secondary ion mass spectrometry (TOF-SIMS), optical microscopy and galvanostatic measurements. On one hand, the small-sized Sn2+ cations can tighten the lattice structure to enhance the Pb/Sn-X (X=I and Br) ionic bonds, thereby effectively immobilizing the halide ions. On the other hand, Sn substitution can significantly reduce anti-site defects, such as ICs and IPb, which are considered potential pathways for ion migration. With these advantages, ion migration is greatly suppressed in Sn-Pb alloyed inorganic perovskites, resulting in reduced hysteresis and improved operational stability of PSC devices.